URGENSI MURAJA’AH DALAM MEMPERTAHANKAN KUALITAS HAFALAN BAGI PENGHAFAL AL-QUR’AN - Ummi Sari Melina Harahap; Sawaluddin Siregar (Amsal Al-Qur’an: Jurnal Al-Qur’an dan Hadis, 2026)
This study was motivated by the problem of decreasing quality of memorization of the Qur'an in memorizers of the Qur'an after the memorization process is completed, which is caused by a lack of consistency in muraja'ah. The purpose of this study is to examine the urgency of muraja'ah and identify effective muraja'ah methods to maintain the quality of memorization. This study uses a literature study method by analyzing verses of the Qur'an, hadith, and literature related to muraja'ah. The results of the study indicate that muraja'ah is very urgent to maintain the strength, accuracy, and understanding of memorization of the Qur'an. Effective muraja'ah methods include daily, weekly, and monthly muraja'ah, as well as the use of variation methods such as reading alone, together, or listening to recordings. This study recommends the application of consistent and scheduled muraja'ah methods to maintain the quality of memorization of the Qur'an in the long term.